Preparação de compostos lamelares: síntese do hidrogenofosfato de zircônio cristalino e sua intercalação com aminas. Um experimento para estudantes de graduação - Cardoso,William da Silva (2005)
The present paper describes the synthesis of crystalline zirconium hydrogen phosphate by direct precipitation and its intercalation with pyridine and n-butylamine. The simple experiment was tested in the undergraduate inorganic chemistry laboratory course for chemistry students at IQ-UNICAMP using inexpensive reagents. The materials were characterized by powder X-ray diffraction and infrared analyses in order to obtain detailed information of the solid structure changes as a result of the intercalation process. Pyridine and n-butylamine are focused in this work as clear and elucidative examples leading to acid-base interactive processes that result in the well-formed infinite sequence of inorganic lamellar structures.